Multi Akad pada Praktek Arisan Online untuk Pembelian Jam Tangan (Studi Kasus Akun Instagram Safa.Watch12) - Nopiyana, Dina (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
This study aims to analyze the Islamic law perspective on online gatherings for purchasing watches, using a case study of the Instagram account @safa.watch12. The research is field-based (Field Research). The findings reveal that, under Islamic law, the validity of the arisan (community-based savings group) is upheld if the goods received are in accordance with the stipulated provisions, such as the Alexandre Christie watches. However, the arisan law becomes invalid if the watches are replaced with another brand, especially when participants are unwilling, as the terms of the arisan prohibit resignation. Participants must receive the watches agreed upon at the time of the social gathering, and any discrepancy between the received goods and the original deposit violates the conditions, as the funds collected are specifically designated to purchase only Alexandre Christie brand watches.